2023
DOI: 10.1088/1755-1315/1198/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Technology Development and Numerical Model Equation for Ocean Current Energy

Abstract: Scope for of research publications on ocean current energy has increased, resulting in high innovation from ocean energy technology and available models for numerical equations in article publications. Reviews for mapping studies on the development of technology and numerical equations are still rarely carried out. This review refers to articles that use equipment used at sea and are based only on ocean currents for research. From a variety of results of the investigation, it can be expected to be used as mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Vertical turbines can rotate from all directions when the ocean currents come so that the amount of energy extracted will be more and more stable. At the same time, horizontal turbines cannot rotate from all directions when the ocean currents come, so the energy extracted is less [8][9][10][11]. Based on the actual conditions at sea, it is true that ocean currents move from various directions.…”
Section: Introduction / Uvodmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical turbines can rotate from all directions when the ocean currents come so that the amount of energy extracted will be more and more stable. At the same time, horizontal turbines cannot rotate from all directions when the ocean currents come, so the energy extracted is less [8][9][10][11]. Based on the actual conditions at sea, it is true that ocean currents move from various directions.…”
Section: Introduction / Uvodmentioning
confidence: 99%
“…Analysis by modifying blades has been carried out for the fi rst time by Gorlov [13], and the results show that it can increase the maximum power coeffi cient up to 0.35 by changing the shape of a straight blade into a helical blade. Kirke and Lazauskas [8] carried out the research by modifying the rotor, and the results have shown to increase the maximum power coeffi cient up to 0.32 by changing the fi xed variable to passive. The foil, blade, and rotor are the most vital components of the turbine, so if modifi ed, it will aff ect the geometric shape, and its performance may increase or decrease.…”
Section: Introduction / Uvodmentioning
confidence: 99%